Proximal seminal vesicle displacement and margins for prostate cancer radiotherapy. Issue 3 (12th January 2021) - Lim Joon, Daryl; Chao, Michael; Piccolo, Angelina; Schneider, Michal; Anderson, Nigel; Handley, Monica; Benci, Margaret; Ong, Wee Loon; Daly, Karen; Morrell, Rebecca; Wan, Kenneth; Lawrentschuk, Nathan; et al.
Abstract: Introduction: Guidelines recommend that the proximal seminal vesicles (PrSV) should be included in the clinical target volume for locally advanced prostate cancer patients undergoing radiotherapy. Verification and margins for the prostate may not necessarily account for PrSV displacement. The purpose was to determine the inter‐fraction displacement of the PrSV relative to the prostate during radiotherapy. Methods: Fiducials were inserted into the prostate, and right and left PrSV (RSV and LSV) in 30 prostate cancer patients. Correctional shifts for the prostate, right and left PrSV and pelvic bones were determined from each patient's 39 daily orthogonal portal images relative to reference digitally reconstructed radiographs. Results: There was a significant displacement of the RSV relative to the prostate in all directions: on average 0.38 mm (95% confidence interval (CI) 0.26 to 0.50) to the left, 0.80–0.81 mm (CI 0.68 to 0.93) superiorly and 1.51 mm (CI 1.36 to 1.65) posteriorly. The LSV was significantly displaced superiorly to the prostate 1.09–1.13 mm (CI 0.97 to 1.25) and posteriorly 1.81 mm (CI 1.67 to 1.96), but not laterally (mean 0.06, CI −0.06 to 0.18). The calculated PTV margins (left–right, superior–inferior, posterior–anterior) were 4.9, 5.3–5.6 and 4.8 mm for the prostate, 5.2, 7.1–8.0 and 9.7 mm for the RSV, and 7.2, 7.5–7.6 and 8.6 mm for the LSV. Conclusion: There is a significant displacement of the PrSV relative to the prostate during radiotherapy. Greater margins are recommended for the PrSV compared to the prostate. Abstract : Seminal vesicles displacement is greater than that of the prostate during radiotherapy and requires a greater margin.